Pengaruh Fasilitas dan Word of Mount terhadap Keputusan Menginap pada Hotel Al-Istiqamah Pasaman Barat - Lorenzo, Naufal; Putra, Trisna (Lembaga Yasin AlSys, 2023)
In the hospitality industry, facilities are important because the decision to choose a hotel is influenced by both online promotions and word of mouth. The aim of this research was to analyze the effect of facilities and word of mouth on the decision to stay at the Al-Istiqamah Hotel, West Pasaman. This research is a quantitative research using causal associative method. In this study, to collect data using questionnaires to guests who have stayed at the Al-Istiqamah Hotel, West Pasaman. The questionnaire can be in the form of a statement to the respondent. Testing the reliability of research using reliability analysis with the help of SPSS version 25.00. From the results of this study the independent variable that has a large influence is word of mouth with a coefficient of 0.420 followed by facilities with a coefficient of 0.362. The t test results from the facility (X1) obtained t count of 5.301 from a significance of 0.05 obtained t table of 0.2061 and the results of the t test for word of mouth (X2) obtained t count of 5.647 from a significance of 0.05 obtained t table 1.987 which can be concluded that t count> t table. Thus the first hypothesis can be accepted, namely that there is a significant influence of the facilities and word of mouth variables on the decision to stay at Hoel Al-Istiqamah, Pasaman Barat.